Application of insurance modelling tools to climate change adaptation decision-making relating to the built environment. Issue 4 (2nd April 2016) - Walker, George R.; Mason, Matthew S.; Crompton, Ryan P.; Musulin, Rade T.
Abstract : Decision-making concerned with managing the possible increased risk of disasters arising from climate change requires tools to forecast changes in disaster risk with time. These changes will be a function of the projected changes not only in weather-related hazard activity due to climate change but also in the vulnerability of the built environment and the aggregate value of assets exposed due to the growth of communities and associated increased concentrations of wealth. Tools developed for the insurance industry over the past three decades to assist decision-makers in estimating and managing catastrophe insurance risk can be adapted to assess the impact of these changes. This paper presents a probabilistic method for undertaking cost–benefit analyses of proposed building adaptation measures using these insurance-based models. The approach accounts for the direct and indirect cost of disasters on a community, including the transfer of risk through insurance and the associated aleatory and epistemic risks. A simplified hypothetical case study focussed on the impact of potential changes to structural design standards for tropical cyclone winds is presented to demonstrate the application of the proposed approach.